Executive Incentives, Profitability Against Tax Avoidance: A Study Of Banking Companies In Indonesia - Nugroho, Wawan Cahyo; Suprapto, Fitria Magdalena (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Many parties contribute taxes to the State, one of which is companies. In calculating company profits, tax costs are very important because taxes are a cost account that can reduce the amount of profit the company earns during the year. The greater the tax paid to the state treasury, the less profit the company generates. This research aims to examine: executive incentives and profitability on tax avoidance. The population in this research are banking companies listed on the Indonesia Stock Exchange in 2017-2020. Sampling using purposive sampling, obtained 26 samples. This research uses multiple linear regression techniques. The results of this research indicate that executive incentives have no effect on tax avoidance because the compensation system without a share basis that applies to companies in Indonesia is less effective in motivating executives to avoid corporate taxes. In companies that manage corporate governance well, alignment between the interests of shareholders and executives through increasing compensation does not apply, so that increasing executive compensation has no effect on tax payments. Profitability has a significant negative effect on tax avoidance because companies that earn profits are assumed not to practice tax avoidance because they are able to manage their income and tax payments.